Iron alters Ca2+ homeostasis in doxorubicin‐resistant K562 cells. (24th March 2020) - Yalcintepe, Leman; Erdag, Demet; Akbas, Fahri; Kucukkaya, Bahire
Abstract: Iron is an essential trace element especially in cell proliferation, and growth for various cellular events. An increasing amount of research has shown that iron metabolism is altered in tumour cells which usually have rapid growth rates. However, the number of studies on iron metabolism, and calcium regulation are limited in drug‐resistant tumour cells. Previously, we have shown that modulation of iron metabolism through iron chelation regulated the intracellular calcium, and increased the doxorubicin sensitivity. In the present study, we investigated the effects of iron on mRNA expression profiles of fifteen key genes (IP3 R1/2/3, RYR1/2, SERCA1/2/3, NCX1/2/3, PMCA1/2/3, and PMCA4) related to calcium homeostasis in the parental cell line K562 and its subclone doxorubicin‐resistant K562 cells. According to the ΔΔCt method with a two‐fold expression difference ( P < .05) as a cut‐off level, although iron showed differential effects on most of the genes, IP3 R and PMCA genes were especially determined to have changed significantly. These results show that iron metabolism is an important metabolism due to changes in the expression of genes involved in calcium regulation and is a new perspective to overcome cancer/drug resistance.